Istiratijiyyat Ta’allum al-‘Arabiyyah ‘Ala Dhau’I Asalib at-Ta’allumi fi Markaz al-Lughat bi Jami’ati Antasari al-Islamiyyah al-Hukumiyyah Banjarmasin - Lailatun Nazifah; Faisal Mubarak Saif; Ridha Darmawaty (University of Darussalam Gontor, 2021)
Learning strategies are essential in learning. On the other hand, learning styles are also an essential step in learning activities that have a positive relationship with learning outcomes. this study aims to uncover various student strategies in learning Arabic based on their learning styles. This research is qualitative research, with the research subjects being 20 students of UPB Group 22 in 2019. The data collection instruments in this study were questionnaires and interviews. The data processing techniques in this descriptive analysis research are data reduction, data presentation, and conclusion drawing. This study indicates that students' learning strategy with a visual learning style tendency is that they need to see things visually to make it easier to understand and understand so that they are more comfortable learning with the use of colors, lines, and shapes. Students with visual tendencies remember what they see more than what they hear and prefer reading rather than being read. The learning strategy of auditory students is to rely more on hearing to receive information and knowledge so that students in this type will find it easier to remember what they hear than what they see, prefer to read with sound, and find it difficult to do tasks involve visuals. Finally, the learning strategy of students with a kinesthetic learning style is learning by involving movement. They find it easier to learn something, not just reading, but also practicing it by doing it or touching particular objects.